Origins and cavity-based regulation of optical anisotropy of α-MoO3 crystal. (1st January 2023) - Shen, Wanfu; Yu, Yu; Huang, Yufeng; Ma, Guoteng; Yao, Chengyuan; Sun, Lidong; Hu, Chunguang
Abstract: Orthogonal α -MoO3 is one of the most common and air-stable compounds of molybdenum, holding the merits of wide bandgap, van der Waals (vdW) structure, biaxial symmetry and recently discovered hyperbolic topological transitions, which has drawn significant attention in developing novel nanophotonic and optoelectronic devices. Herein the broadband optical anisotropy, one of the most fundamental physical characteristics of α -MoO3 crystal, was systematically investigated using a combination of spectroscopic ellipsometry (SE) and reflectance difference spectroscopy (RDS). The centimeter-level high-quality α -MoO3 crystal was grown by modified physical vapor deposition. The optical refractive indices along three crystalline axes were precisely determined by SE in the broad spectral range (400–1600 nm), and then the in-plane and out-plane birefringence was analyzed. Both the intrinsic and resonant cavity modulated optical anisotropy of α -MoO3 was studied by polarization-resolved RDS, from which we find the physical origins of linear dichroism are dominated by electronical transitions along the c -axis. Furthermore, the external photonic cavity of SiO2 enables enhanced sensitivity to view electronical transitions and a high modulation ratio of optical anisotropy reached 30, which provides new opportunities to tune optical anisotropy for polarized photonic devices. Our results can help understand the physical origin of the highly optical anisotropy of α -MoO3 and establish an effective metrological tool to study other types of vdW crystals.